2010
DOI: 10.1177/1933719110377471
|View full text |Cite
|
Sign up to set email alerts
|

Generation of an Osteogenic Graft From Human Placenta and Placenta-Derived Mesenchymal Stem Cells

Abstract: The objective of the study was to determine the feasibility of generating a biodegradable, stem cell-loaded osteogenic composite graft from human placenta. Initially, a scaffold from human chorion membrane was produced. Human placenta mesenchymal stem cells (MSCs) derived from either first-trimester chorionic villi or term chorion membrane were differentiated osteogenically on this scaffold. Outgrowth, adherence, and osteogenic differentiation of cells were assessed by immunohistochemistry (IHC), scanning elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Chorionic mesenchymal stem cells can undergo osteogenic [54] and neuronal differentiation [55]; yet the stemness of chorionic mesenchymal cells is uncertain at this time. Immunofluorescence studies have not demonstrated SSEA-3 and SSEA-4 in these cells [56].…”
Section: Discussionmentioning
confidence: 99%
“…Chorionic mesenchymal stem cells can undergo osteogenic [54] and neuronal differentiation [55]; yet the stemness of chorionic mesenchymal cells is uncertain at this time. Immunofluorescence studies have not demonstrated SSEA-3 and SSEA-4 in these cells [56].…”
Section: Discussionmentioning
confidence: 99%
“…There is however, limited work on placenta-derived stem cells. Surbek's group showed both first trimester and term chorionic stem cells were capable of generating osteogenic grafts [67], indicating the potential of these cells in regenerative medicine. Furthermore, another study showed engraftment of term placental adherent cells inhibited growth of multiple myeloma in bone and stimulated bone formation in an immune-deficient model of medullary myeloma bone disease [68].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, P-MSCs cultured in hCBS were differentiated into mesenchymal and ectodermal lineages, indicative of multiple/pluri-potent characteristics. A recent study showed that P-MSCS were less prone to osteogenic differentiation and expressed a lower level of CD146 when compared with MB-MSCs (34), yet another study showed successful generation of an osteogenic graft from P-MSCs (35). It appears that the expression of phenotypes and functions by P-MSCs may vary when being cultured in different conditions or being isolated from different tissue origins.…”
Section: Discussionmentioning
confidence: 99%